2005
DOI: 10.1055/s-2004-830243
|View full text |Cite
|
Sign up to set email alerts
|

Über eine pulmonale Infektion durch Mycobacterium malmoense

Abstract: Nicht-tuberkulöse Mykobakterien gewinnen als Infektionserreger beim Menschen zunehmend an Bedeutung.Neben Mycobacterium (M.) avium-intracellulare ist hier vor allem M. malmoense zu nennen. AbstractM. malmoense could be cultivated in sputum samples of a 49-year-old patient with destructive pulmonary disease. The conventional antituberculous therapy (started because initially a presumptive diagnosis of tuberculosis was established) was altered to ethambutol, rifabutin, clarithromycin and ciprofloxacin, followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In addition, some reports stated that pulmonary M. malmoense infection was mainly complicated by chronic obstructive lung disease, such as pneumoconiosis, chronic airway infection, or pulmonary emphysema (7,8,9). Moreover, it was reported that M. malmoense infection was usually observed among HIV-negative people (2,10 (2,10,11,(13)(14)(15) …”
Section: F I G U R E 3 Mi C R O S C O P I C H I S T O P a T H O L Omentioning
confidence: 99%
“…In addition, some reports stated that pulmonary M. malmoense infection was mainly complicated by chronic obstructive lung disease, such as pneumoconiosis, chronic airway infection, or pulmonary emphysema (7,8,9). Moreover, it was reported that M. malmoense infection was usually observed among HIV-negative people (2,10 (2,10,11,(13)(14)(15) …”
Section: F I G U R E 3 Mi C R O S C O P I C H I S T O P a T H O L Omentioning
confidence: 99%